Electrocardiographic predictors of long-term outcomes after radiofrequency ablation in patients with right-ventricular outflow tract tachycardia - Krittayaphong, Rungroj; Sriratanasathavorn, Charn; Dumavibhat, Chatkanok; Pumprueg, Sachana; Boonyapisit, Warangkana; Pooranawattanakul, Sukanya; Phrudprisan, Suteera; Kangkagate, Charuwan (Europace (London, England), 2006)
The objectives of this study were to identify electrocardiographic (ECG) predictors of long-term outcomes after radiofrequency (RF) ablation in patients with right-ventricular outflow tract (RVOT) tachycardia. We correlated ECG characteristics with RF ablation outcomes in 144 patients with RVOT tachycardia who underwent RF ablation for >1 year. Unfavourable RF ablation outcomes were predefined as unsuccessful RF ablation or recurrence of tachycardia requiring repeated ablation. RF ablation was not successful in 11 (7.6%) patients and 16 (12%) patients had arrhythmia recurrence requiring repeated ablation. Average follow-up time was 72.2+/-28.4 months. Selected parameters from univariate analysis included number of RF applications, pacemapping, application of bonus burn, procedure time, monophasic R-wave in lead I, QS pattern in leads I and aVL, QRS duration in leads II and V(2), and right axis deviation, in ventricular tachycardia. From logistic regression analysis, only monophasic R-wave in lead I remained in the final equation (P=0.004, odds ratio 12.9). Monophasic R-wave in lead I during RVOT tachycardia is associated with unfavourable outcomes after RF ablation. This finding may help clinicians in the selection of patients for RF ablation and for the prediction of RF ablation outcome.